The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12965/jer.19.38652.326
|View full text |Cite
|
Sign up to set email alerts
|

The effectivity of pharyngeal strengthening exercise, hyolaryngeal complex range of motion exercise, and swallowing practice in swallowing function of ischemic stroke patients with neurogenic dysphagia

Abstract: Dysphagia is associated with an increased risk of aspiration pneumonia which often results in death in stroke patients. Therefore, effective and efficient management is important. Behavioral therapy for swallowing rehabilitation based on the principles of neuroplasticity such as oropharyngeal strengthening and range of motion exercises are the alternative ones that often be used. This study aimed to assess the changes in swallowing function in ischemic stroke patients with neurogenic dysphagia after pharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…The goal of dysphagia rehabilitation through use of rTMS, tDCS, NMES, PES, and TDT in stroke patients is promoting brain cortical neuroplasticity ensuring effective swallowing and prevention of aspiration/penetration. 33 -36 Our study findings showed that frequency, number of sessions, and duration of the combined and single neurostimulation and traditional therapies as significant moderator variables in the current NMA. A recent systematic review has revealed that frequency, duration, intensity, and repetitions of the dysphagia therapies as important dysphagia exercise dose-determining factors to ensure better dysphagia-related outcomes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The goal of dysphagia rehabilitation through use of rTMS, tDCS, NMES, PES, and TDT in stroke patients is promoting brain cortical neuroplasticity ensuring effective swallowing and prevention of aspiration/penetration. 33 -36 Our study findings showed that frequency, number of sessions, and duration of the combined and single neurostimulation and traditional therapies as significant moderator variables in the current NMA. A recent systematic review has revealed that frequency, duration, intensity, and repetitions of the dysphagia therapies as important dysphagia exercise dose-determining factors to ensure better dysphagia-related outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…The current NMA findings suggest that the therapeutic effects produced by combined neurostimulation and traditional dysphagia therapies promote and induce better cortical plasticity and reorganization of the central nervous system and neural activation of oropharyngeal muscles leading to better swallowing function and reduction of PTT and OTT. 35,36 Additionally, the activation of oropharyngeal muscles ensures improved precision, safety, performance, and coordination of the bolus movement from the oropharyngeal phases into the esophageal phase. In the current NMA, PES alone had the lowest therapy ranking suggesting limited therapeutic effect in improving PSD complications.…”
Section: Effectiveness Of Neurostimulation and Traditional Dysphagia ...mentioning
confidence: 99%
“…Terdapat peningkatan PAS dan FOIS setelah intervensi. Oleh karena itu, intervensi dapat disarankan untuk digunakan sebagai salah satu perawatan untuk meningkatkan fungsi menelan pada pasien stroke iskemik dengan disfagia neurogenik (Kusumaningsih, Lestari, Harris, Tamin, & Werdhani, 2019).…”
Section: Manuver Mendelsohnunclassified
“…Manuver ini juga konsisten dengan konsep kekhususan yang menyatakan bahwa wilayah tubuh bersaing untuk mendapatkan representasi di korteks dan penggunaan bagian tubuh dapat meningkatkan keterwakilannya. Stimulasi yang sering dan berulang ini adalah salah satu dasar untuk intervensi bahwa sesuai dengan prinsip neuroplastisitas (Kusumaningsih, Lestari, Harris, Tamin, & Werdhani, 2019).…”
Section: Manuver Mendelsohnunclassified
“…Kąsnis ryjamas porą kartų, kai matomi tokie simptomai, kaip nepakankamas liežuvio šaknies atitraukimas, ribotas gerklų pakilimas ir ryklės raumenų susitraukimas(Kusumaningsih et al, 2019).…”
unclassified